VD_FINDINFO AI 281/10 - 342/2011 vom 14. Juli 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, FORCE PROBANTE, RAPPORT MÉDICAL, REVENU D'INVALIDE | 28 al. 2 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA